Nutritional control of body size through FoxO-Ultraspiracle mediated ecdysone biosynthesis - Koyama, Takashi (2016)
Despite their fundamental importance for body size regulation, the mechanisms that stop growth are poorly understood. In Drosophila melanogaster, growth ceases in response to a peak of the molting hormone ecdysone that coincides with a nutrition-dependent checkpoint, critical weight. Previous studies indicate that insulin/insulin-like growth factor signaling (IIS)/Target of Rapamycin (TOR) signaling in the prothoracic glands (PGs) regulates ecdysone biosynthesis and critical weight. Here we elucidate a mechanism through which this occurs. We show that Forkhead Box class O (FoxO), a negative regulator of IIS/TOR, directly interacts with Ultraspiracle (Usp), part of the ecdysone receptor. While overexpressing FoxO in the PGs delays ecdysone biosynthesis and critical weight, disrupting FoxO-Usp binding reduces these delays. Further, feeding ecdysone to larvae eliminates the effects of critical weight. Thus, nutrition controls ecdysone biosynthesis partially via FoxO-Usp prior to critical weight, ensuring that growth only stops once larvae have achieved a target nutritional status.